MHC genotyping from next-generation sequencing: detailed methodology for the gidgee skink, Egernia stokesii. Issue 2 (2nd July 2016) - Pearson, S. K.; Bradford, T. M.; Ansari, T. H.; Bull, C. M.; Gardner, M. G.
ABSTRACT: Next-generation sequencing has revolutionised molecular ecology. Its key advantages are a more accurate representation of genetic variation made possible by the generation of large volumes of data, more quickly and at a lower price per sequence than traditional sequencing methods. Yet these benefits come with a cost. For example, next-generation sequencing is error prone and requires increased quality control compared with traditional methods. Problems associated with next-generation sequencing may be exacerbated when sequencing gene complexes such as the major histocompatibility complex (MHC). Although not eliminated, significant progress has been made in addressing some of those problems and there is an increasing literature utilising this technology for studies of the MHC. However, what is generally lacking is detailed documentation of the methods used, and clear reasoning, for each step. Here we document detailed methodology, using an Australian lizard, Egernia stokesii, as a case study, with explanations, for MHC amplification, sequencing and allele identification. This work provides molecular ecologists with a comprehensive guide to follow, particularly when first employing next-generation sequencing techniques similar to those used here. In addition, the E. stokesii MHC genotypes derived from this work provide foundation data for future investigations of the influence of social structure on the MHC.